Determinants of Students’ Mathematics Achievement: The Roles of Critical Thinking, Self-Efficacy, and Metacognitive Awareness Through Achievement Motivation - Anwar Sadat; Syamsu Alam; Ma'rufi Ma'rufi; Taufiq Taufiq (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examines whether students’ internal factors, namely critical thinking ability, self-efficacy, and metacognitive awareness, contribute to mathematics achievement directly and indirectly through achievement motivation. This study therefore aimed to analyze the direct and indirect effects of critical thinking ability, self-efficacy, and metacognitive awareness on mathematics achievement through achievement motivation among 121 eighth-grade students. A quantitative ex post facto design was employed, and the data were analyzed using path analysis to investigate the proposed causal relationships. Descriptive findings showed that students’ critical thinking ability was at a moderate level (M = 75.6), self-efficacy was high (M = 61.5), metacognitive awareness was high (M = 89.3), and achievement motivation was moderate (M = 58.4). However, mathematics achievement was also only at a moderate level (M = 59.6). The results revealed that critical thinking ability had a significant direct effect on mathematics achievement (β = 0.1470, p = 0.045). By contrast, self-efficacy (β = -0.0906, p = 0.785), metacognitive awareness (β = 0.0927, p = 0.561), and achievement motivation (β = 0.3753, p = 0.141) did not show significant direct effects on mathematics achievement. In the first path model, only self-efficacy (β = 0.9256, p < 0.001) and metacognitive awareness (β = 0.1274, p = 0.027) significantly predicted achievement motivation. Overall, the model explained only 3.07% of the variance in mathematics achievement (R² = 0.0307). These findings indicate that critical thinking ability is the only variable in the model that significantly predicts mathematics achievement, while other factors outside the model may have a more substantial role.